Thermal relationships between body temperature and environment conditions set upper distributional limits on oviparous species - Medina, Susana Marlin (2011)
We determined the thermal biology of the oviparous Liolaemus boulengeri and the viviparous Liolaemus lineomaculatus populations localised at high and low latitude sites in Patagonia, Argentina. We present data of body temperatures in the field (Tb) and preferred temperature in the laboratory (Tpref), micro-environmental and operative temperatures and the effectiveness of thermoregulation. Liolaemus boulengeri and L. lineomaculatus choose different heat sources for active selection of suitable thermal micro-environments for thermoregulation, and the oviparous L. boulengeri is a more effective thermoregulator (E=0.55) than the viviparous L. lineomaculatus (E=0.43). Even when L. boulengeri is a better thermoregulator and both species show identical timing in the reproductive cycles, there are constraint factors that impose limitations on the southernmost distribution of the oviparous L. boulengeri.